Quality of Life (QOL) Pasien Hipertensi Usia Dewasa Muda yang Menjalani Pengobatan di Rumah Sakit Kota Makassar - Yunus, Nurfaizin; Maria, Ida Leida; Russeng, Syamsiar S (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2020)
The prevalence of hypertension experienced a shifting of cases from old to young, and contributes to the increase in the age group at risk. Young adult is a population very productive so indispensable effort to continue to obtain good quality of life. The aim of the research was to find out the risks of obesity, type D personality, anger expression, family support and treatment obedience on the quality of life of young adult hypertension patients in several hospitals of Makassar City. Design of the research is analytic observational with retrospective cohort study. The samples comprised 73 patients with the consecutive sampling technique. Data were analyzed using RR test and multiple logistic regressions. The results of the research indicate that the significant risking factors affecting the quality of life of young adult hypertension patients are obesity (RR= 1.942; 95%CI: 1.222-3.055), type D personality (RR = 2.782; 95%CI: 1.647-4.699), anger in (RR= 2.464; 95%CI: 1.384-4.395), anger control (RR= 1.920; 95% CI: 1.203-3.063), family support (RR= 2.920; 95%CI: 1.773-4.809) and treatment obedience (RR = 4.047; 95%CI: 1.770-9.249), while the insignificant risk factor is anger out (RR= 1.226; 95%CI: 0.644-2.333). The conclusion obesity, type D personality, anger in, anger control, family support and treatment obedience are risk factors for quality of life. Factor most at risk is obesity.